2022
DOI: 10.1108/jaee-12-2021-0411
|View full text |Cite
|
Sign up to set email alerts
|

Value relevance of accounting earnings and cash flows in a transition economy: the case of Serbia

Abstract: PurposeThe purpose of the study is to investigate the association of earnings and cash flows with stock prices and returns, and the impact of regulatory changes on the value relevance of accounting numbers.Design/methodology/approachThe authors examine a sample of non-financial firms listed on the Belgrade Stock Exchange from 2005 to 2018 and use three regression models – price, return and differenced.FindingsThe authors find evidence that accounting earnings are more value relevant than cash flows. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Chen et al (2001) have reported that book value and earnings are value-relevant in various segments of the Chinese stock market based on empirical evidence from 1991 to 1998. Other researchers (Ragab and Omran, 2006;Bae and Jeong, 2007;Pourheydari, Aflatooni, and Nikbakhat, 2008;Al-Hares, AbuGhazaleh, and Haddad, 2012;Bilgic and _ Ibis, 2013;Omokhudu and Ibadin, 2015;Ahmadi and Bouri, 2018;Rahman and Liu, 2021;Srivastava and Muharam, 2021;Cupic et al, 2022) have found similar results in different global markets. Ragab and Omran (2006) have conducted research to examine the relevance of earnings value and book value in the Egyptian Stock Market from 1998 to 2002.…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 74%
See 2 more Smart Citations
“…Chen et al (2001) have reported that book value and earnings are value-relevant in various segments of the Chinese stock market based on empirical evidence from 1991 to 1998. Other researchers (Ragab and Omran, 2006;Bae and Jeong, 2007;Pourheydari, Aflatooni, and Nikbakhat, 2008;Al-Hares, AbuGhazaleh, and Haddad, 2012;Bilgic and _ Ibis, 2013;Omokhudu and Ibadin, 2015;Ahmadi and Bouri, 2018;Rahman and Liu, 2021;Srivastava and Muharam, 2021;Cupic et al, 2022) have found similar results in different global markets. Ragab and Omran (2006) have conducted research to examine the relevance of earnings value and book value in the Egyptian Stock Market from 1998 to 2002.…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 74%
“…Several empirical research studies have examined the value relevance of accounting information using the pricing model in established markets based on Ohlson’s theoretical framework for valuation. These studies model market value as a function of book value and reported earnings in addition to evaluating the value relevance of earnings and book value (Bettman et al , 2006; Brief and Zarowin, 1999; Collins et al , 1997; Cupic et al , 2022; Barth et al , 1996; Bernard, 1995; Stark and Thomas, 1998).…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation